KUALITAS DARI PROSEDUR PENGENDALIAN INTERNAL: LIMA BENTUK PENGENDALIAN COSO DAN PENGARUH MODERATING 1 PADA KEADILAN ORGANISASIONAL DAN KECURANGAN KARYAWAN PADA PERUSAHAAN DI KOTA SEMARANG - Irma Setyani; Aditya Septiani (Diponegoro Journal of Accounting, 2014)
This study aims to examine the empirical invidence of impact factors on the quality ofinternal control procedure in Semarang the finance company, in this case, a Bank Perkreditan Rakyat or BPR and BUMN especially in tellecommunication sectors. The factors were, perceptions of organizational justice, control environment, risk management, information and communication, monitoring and employee fraud.This study used primary data, which was, using distributed questionnaires at company sample. The collecting data method using purposive sampling in total sample 7 (seven) company samples and the number of respondent in minimum 80 respondents. In this study there were two theoretical framework. The first theoretical framework tested with logistic regression analysis, while the second theoretical framework tested with multiple linear regression analysis.Based on the result of, the first model framework shows that quality of internal controling procedures and perception of justice organizational has a significant effect on employee fraud. The second theoretical framework shows the result of control environment, risk management and controling activity has a positively impact on the quality of internal control procedures so that hypothesis accepted, while the information and communication, and monitoring has a negatively impact on the quality of internal control procedures so that hypothesis rejected.